Using knowledge translation to support the use of evaluation findings: A case study of the linda mama free maternity program in Kenya. - Fatuma H Guleid; Stacey Orangi; Angela Kairu; Brian Arwa; Janet Keru; Anne Musuva; Ileana Vilcu; Anooj Pattnaik; Nirmala Ravishankar; Edwine Barasa (PLOS Global Public Health)
Using program evaluation findings is crucial in improving health programs and realising the program's benefits. In this article, we report on how a knowledge translation (KT) approach supported the use of evaluation findings to improve the Linda Mama free maternity program in Kenya. We used a case study design employing qualitative approaches to describe our KT strategy and its impact on evaluation use. Data were collected through semi-structured in-depth interviews of participants (n = 25) in three Kenyan counties following dissemination of the evaluation findings and co-production of action plans based on the evaluation. The findings suggest modest improvements in the implementation of Linda Mama in 3 Kenyan counties facilitated by application of the evaluation findings. However, these improvements were not uniform across and within the counties. Challenges such as the COVID-19 restrictions, lack of infrastructure and delayed reimbursement of funds hindered the full implementation of the action plans. The KT strategy was a key facilitator for the improvements. The dissemination and deliberation workshops provided learning spaces for stakeholders, ensuring that each perspective was considered. The participatory method used in developing the action plans also improved communication between stakeholder groups. Participants reported that this approach made aware them of the gaps in implementation and motivated them to realise the full potential of the Linda Mama program. Using KT, especially when evaluating and refining the implementation of complex health programs with multiple stakeholders, is useful in improving the uptake of evaluation findings. However, it can be challenging to sustain such engagement with stakeholders. In addition, contextual factors that affect uptake need to be considered and navigated. Finally, significant investment (both in human resource and financial) in such approaches is required if KT is to be successful.